A Rare Case of Acute Pancreatitis as Dengue Complication - Tuy Hong Thi Nguyen; Hien Quang Nguyen (Case Reports in Infectious Diseases)
A 31-year-old male was admitted to the hospital because of fever for 2 days. He also had chills, headaches, muscle aches, fatigue, and diarrhea. His vital signs were stable. Dengue virus nonstructural protein 1 (NS1) antigen was positive. Laboratory tests were significant for thrombocytopenia of 67.000/mm3 and high hematocrit of 45%. On the fifth day of the onset of fever, he experienced sudden epigastric pain. Laboratory results showed elevated serum amylase and lipase. Noncontrast abdominal CT findings were consistent with acute pancreatitis, Balthazar grade D. The patient was managed with supportive care and bowel rest. Two days later, his condition became stable, and he was discharged without complications.